2017
DOI: 10.1001/jamapediatrics.2017.0250
|View full text |Cite|
|
Sign up to set email alerts
|

Child and Adolescent Health From 1990 to 2015

Abstract: Importance Comprehensive and timely monitoring of disease burden in all age groups, including children and adolescents, is essential for improving population health. Objective To quantify and describe levels and trends of mortality and nonfatal health outcomes among children and adolescents from 1990 to 2015 to provide a framework for policy discussion. Evidence Review Cause-specific mortality and nonfatal health outcomes were analyzed for 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(95 citation statements)
references
References 65 publications
4
88
0
3
Order By: Relevance
“…Approximately 60% (588,000) of these were among those aged 15–19. The leading cause of death among 10–14 year olds was HIV/AIDS due to its prevalence in Sub-Saharan Africa and the Caribbean [4] (Fig. 1).…”
Section: Definitions and Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 60% (588,000) of these were among those aged 15–19. The leading cause of death among 10–14 year olds was HIV/AIDS due to its prevalence in Sub-Saharan Africa and the Caribbean [4] (Fig. 1).…”
Section: Definitions and Demographicsmentioning
confidence: 99%
“…The maternal mortality ratio (MMR) for 10–19 year olds is 278 per 100,000, as compared to the global MMR for 25–29 year olds of 132 per 100,000. And the rate of decline in MMR for adolescents has been slower than for other age groups [4]. Given the leading causes of mortality, existing global adolescent health programs focus primarily on HIV and sexual and reproductive health services [5].…”
Section: Definitions and Demographicsmentioning
confidence: 99%
“…The accuracy of chest x-rays in identifying the cause of tachypnea was demonstrated to be relatively poor in India, 27 emphasizing further the need for improved diagnostic tools when assessing children in respiratory distress, especially given that pneumonia continues to account for the greatest burden of mortality in children worldwide. 35 Another diagnostic technology that has revolutionized EM in recent years and is now starting to embed itself into emergency practice worldwide, just as it has in well-resourced settings, is point-of-care ultrasound (POCUS). This year, two high-quality articles were identified that present data on the use of, and training in, POCUS in resource-limited settings.…”
Section: Plos Onementioning
confidence: 99%
“…Pneumonia is a major health problem worldwide. It is one of the leading causes of death and morbidity in children, especially in those under 5 years of age [1,2]. Despite vaccination programs, Streptococcus pneumoniae remains among the main microorganisms involved in bacterial pneumonia, notably in terms of severity [3].…”
Section: Introductionmentioning
confidence: 99%